2020
DOI: 10.1007/s10452-020-09795-5
|View full text |Cite
|
Sign up to set email alerts
|

Meiofauna in stream habitats: temporal dynamics of abundance, biomass and secondary production in different substrate microhabitats in a first-order stream

Abstract: Meiofaunal abundance, biomass and secondary production were investigated over 13 months in an unpolluted first-order stream. Four microhabitats were considered: sediment and the biofilms on dead wood, macrophytes and leaf litter. The relative contribution of the microhabitats to secondary production and the influence of environmental factors on meiofaunal density distribution were estimated. We expected (1) meiofaunal abundance and biomass to exhibit seasonal patterns, with more pronounced seasonal fluctuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Here we found an abundant meiobenthic community dominated by nematodes and rotifers, and the taxonomic composition and abundance values reported in the present http://www.koedoe.co.za Open Access study are quite comparable to meiobenthic communities found in streams and rivers in Europe (e.g. Brüchner-Hüttemann et al 2020;Majdi et al 2012;Majdi, Threis & Traunspurger 2017). Some meiobenthic groups have been previously investigated in the KNP: for example, 30 years ago, Botha and Heyns (1991, 1992, 1993) identified a total of 33 nematode species (including species new to science) in sediment samples collected from Crocodile and Olifants rivers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Here we found an abundant meiobenthic community dominated by nematodes and rotifers, and the taxonomic composition and abundance values reported in the present http://www.koedoe.co.za Open Access study are quite comparable to meiobenthic communities found in streams and rivers in Europe (e.g. Brüchner-Hüttemann et al 2020;Majdi et al 2012;Majdi, Threis & Traunspurger 2017). Some meiobenthic groups have been previously investigated in the KNP: for example, 30 years ago, Botha and Heyns (1991, 1992, 1993) identified a total of 33 nematode species (including species new to science) in sediment samples collected from Crocodile and Olifants rivers.…”
Section: Discussionsupporting
confidence: 86%
“…Among those benthic invertebrates, one may further make a distinction between the macrobenthos, such as aquatic insects, snails and leeches that are large enough to be visible and usually are retained on 500 μm meshes, and the meiobenthos, such as nematodes, rotifers, copepods and tardigrades that are so tiny that they are invisible and usually pass through 500 μm-meshes but are retained on 20 μm meshes (Ptatscheck, Gehner & Traunspurger 2020a). Meiobenthic invertebrates are little studied although they show complex behaviours and extraordinary physiologies that allow them to colonise most, if not all, benthic habitats (Brüchner-Hüttemann, Ptatscheck & Traunspurger 2020;Rebecchi, Boschetti & Nelson 2020) where they can reach remarkable abundances (between 10 5 -10 6 ind. m -2 on any submerged substrate) (Majdi, Schmid-Araya & Traunspurger 2020;Traunspurger, Wilden & Majdi 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our results may not be directly transferable to real-world ecosystems because our food web model was comparatively simple and consisted of functional groups that were assigned a group-specific tolerance, whereas in real-world ecosystems functional groups can consist of many species with different tolerances (see Appendix A). In addition, our model relies on continuous growth of population biomass that does not account for differences between the growth of population size (i.e., number of individuals) and of individuals as part of their development, whereas in real world ecosystems, developmental cycles, for example, with resting egg stages and near-complete loss of adult biomass in winter, can lead to pronounced biomass cycles (Brüchner-Hüttemann et al, 2020). Thus, the extent to which biological interactions play a role will also depend on the relationship between stressor duration and the generation time of organisms, which can vary strongly from days to years between freshwater insect species (Huryn and Wallace, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Plant and animal communities in slow-moving streams typically resemble those in lentic (lake and pond) habitat. According to Tokeshi and Pinder [18], algae and plants are crucial to lotic systems as a source of energy, for building microhabitats that protect other animals from predators and the current, and as a food source [18,19].…”
Section: The Lotic Ecosystemmentioning
confidence: 99%